Atividade antioxidante de extratos e microencapsulados de feijoa (Acca sellowiana) - Santos, Suelen dos (2018)
The feijoa (Acca sellowiana) belongs to the botanical family Myrtaceae is native to South America, found especially in the Brazilian southern plateau, but is little known in Brazil. Feijoa has several important bioactive and functional compounds, such as antioxidants, vitamins, fibers and minerals. This work aimed to microencapsulate the in natura pulp of feijoa of the cultivar Alcântara in spray dryer. To evaluate the encapsulation efficiency and the antioxidant properties of the microencapsulated extracts and the pulp of the feijoa in natura by the free radical sequestration (2,2- diphenyl-1-picryl-hydrazyl) (DPPH) methods, capture of the 2,2'- azinobis (3- ethylbenzothiazoline-6-sulfonic acid) (ABTS) and iron reducing power (FRAP). The encapsulation efficiency for the sample with the encapsulating agent maltodextrin (MD) was 96.75% and for the gum arabic (GA) sample was 95.72%. The antioxidant activity for the ABTS method showed that the microencapsulated samples had the highest values, in sample GA (2003,667 mmol TEAC g-1) (TEAC: Trolox Equivalent Antioxidant Capacity) and the sample (MD) (1548.667 mmol TEAC g-1) and hydroalcoholic (1452,000 mmol TEAC g-1) aqueous extracts (1948.667 mmol TEAC g-1) followed by acetone (1850.333 mmol TEAC g-1), aqueous (1548.667 mmol TEAC g-1) and hydroalcoholic with (1452,000 mmol TEAC g-1). The highest antioxidant activity by the DPPH method was found in the hydroalcoholic extract (32,455 mmol Trolox g-1), followed by microencapsulated samples, sample (MD) (30.636 mmol Trolox g-1) and sample 1), whereas the extracts with acetone and water had the same activity (19.879 mmol Trolox g-1). In the FRAP method, the hydroalcoholic extract also showed higher activity (66.528 mmol Fe+2 g-1) followed by microencapsulated samples, GA sample (63,408 mmol Fe+2 g-1) and MD sample (58.448 mmol Fe+2 g -1) and aqueous extracts (44,208 mmol Fe+2 g-1) and with acetone (28.088 mmol Fe+2 g -1).